Gender inequality in employment in Mozambique - Carlos Gradín; Finn Tarp (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2017)
We investigate the trend in the gender employment gap in the expanding nonsubsistence sector of the economy in Mozambique, a country still characterized by a large subsistence agricultural sector. We show evidence that the gender gap has widened over time and we identify two factors strongly associated with it. One factor is the still relatively lower level of female human capital, with less attained education, as well as literacy and Portuguese proficiency rates. The lower conditional employment probabilities of married women, as compared with men, is the other factor. These findings point at expanding womens education and facilitating the access of married women to the emerging labour market as the most effective ways of achieving a more inclusive growth path that does not leave women behind.
Keywords: J16; J61; J71; O15; O55; 330; gender; employment; education; Mozambique